THE INFLUENCE OF SOCIALIZATION, FACEBOOK AND INSTAGRAM ON VOTER PARTICIPATION IN THE MAHAKAM ULU DISTRICT ELECTION, EAST KALIMANTAN PROVINCE - Frederik Melawen (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
The motivation behind this study was to figure out 1) Socialization meaningfully affected massive impact on elector support in local head decisions in Mahakam Ulu Rule, 2) Facebook affected huge impact on citizen cooperation in territorial head races in Mahakam Ulu Regime, 3) Instagram affected tremendous impact on elector interest in provincial head races in Mahakam Ulu Rule, 4) Socialization, Facebook and Instagram together have an impact and are critical on elector investment in provincial head decisions in Kab. Mahakam Ulu. This examination strategy utilizes irregular inspecting technique with a sum of 100 respondents, the exploration investigation technique utilized is Numerous Direct Relapse Investigation. The consequences of the review expressed that socialization meaningfully affected citizen support, Facebook meaningfully affected elector investment, Instagram unimportantly affected elector cooperation, while at the same time the socialization factors, Facebook and Instagram significantly affected citizen interest.